Effect of fire on grass and woody species of a Caldén woodland (Semiárida, 2020)
One essay was made in a Prosopis caldenials woodland in order to know the effect of fire on grasses and woody species. Before the fire the weight of fuel was 376 gMS/m2 (desiderable species 30% undesiderable 70%). Twelve months later, standing crop was 208 gMS/m2 (desiderable species 57 %, undesiderable 43 %). Piptochaetium napostaense (flechilla negra) were not so abundant as before it. While the evergreen woody species showed same regrowth, the deciduous species didn it shows anything after six months of fire. Twelve months later the woody species had basal or aerial regrowth. The damage of fire on Prosopis caldenia (caldén) y Condalia microphylla (piquillin) was very important when they had many stems. It was observed that fire didn it kilI the trees and shrubs, but canopy was reduced. Probably it was the reason by which forbs and grasses covered rapidly the soil.